2010
DOI: 10.1074/jbc.m110.118398
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-regulated Protein Lysine Acetylases in Mycobacteria

Abstract: Cyclic AMP synthesized by Mycobacterium tuberculosis has been shown to play a role in pathogenesis. However, the high levels of intracellular cAMP found in both pathogenic and nonpathogenic mycobacteria suggest that additional and important biological processes are regulated by cAMP in these organisms. We describe here the biochemical characterization of novel cAMP-binding proteins in M. smegmatis and M. tuberculosis (MSMEG_5458 and Rv0998, respectively) that contain a cyclic nucleotide binding domain fused to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
178
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(191 citation statements)
references
References 53 publications
9
178
1
Order By: Relevance
“…M. tuberculosis and M. smegmatis encode unique protein lysine acetyltransferases (MtPatA and MsPatA, respectively). In these organisms, the GNAT domain is attached to a cyclic AMP (cAMP) binding domain (type III) (178,191). cAMP allosterically activates MtPatA and MsPatA, enhancing their activity Ͼ2-fold (178,(191)(192)(193)(194).…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
See 1 more Smart Citation
“…M. tuberculosis and M. smegmatis encode unique protein lysine acetyltransferases (MtPatA and MsPatA, respectively). In these organisms, the GNAT domain is attached to a cyclic AMP (cAMP) binding domain (type III) (178,191). cAMP allosterically activates MtPatA and MsPatA, enhancing their activity Ͼ2-fold (178,(191)(192)(193)(194).…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
“…MsPatA acetylates a universal stress protein (USP) (MSMEG_ 4207) at a single lysine residue, and acetylation increases in the presence of cAMP (191). The in vivo significance of USP acetylation was not tested, likely because the function of most USPs is unclear, but there is evidence suggesting that USPs provide resistance to various stressors (reviewed in reference 195).…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
“…The activity of protein acetyltransferases is also controlled by allosteric effects. In M. tuberculosis and Mycobacterium smegmatis, cAMP directly activates the protein acetyltransferases MtKat (Rv0998) and MsKat (MSMEG_5458) by binding to a cyclic nucleotide-binding domain that is fused to the N terminus of the catalytic GNAT domain (5,6).…”
mentioning
confidence: 99%
“…Allosteric effects also control the activity of protein acetyltransferases. In Mycobacterium tuberculosis and Mycobacterium smegmatis, cAMP directly activates the protein acetyltransferases MtKat (Rv0998) and MsKat (MSMEG_5458) by binding to a cyclic nucleotide-binding domain that is fused to the N terminus of the catalytic GNAT domain (20). Recently, we found that an amino acid-binding domain (ACT domain) fused to the GNAT acetyltransferase of Micromonospora aurantica is used to exert amino acid-induced allosteric regulation of the enzyme (21).…”
mentioning
confidence: 99%